Impact of Bacillus subtilis bacterium on the properties of concrete. (2020) - Jena, Shradha; Basa, Bidyadhar; Panda, Kishor Chandra; Sahoo, Naresh Kumar
Abstract: The activity life span of concrete sharply decreases with the formation of cracks on its surface which leads to corrosion of concrete. To deal with such problems newer technologies are being adopted for concrete production and one such high-tech concrete is self-healing concrete by Microbiologically Induced Calcite Precipitation (MICP). This kind of concrete can initiate biological activity to deal with its cracks and to recover itself. This research paper throws light on the experimental investigation carried out to evaluate the impacts of Bacillus subtilis bacteria on concrete properties. The experiment has been carried out using six different bacterial concentrations in the concrete mixes, such as 10, 10 2, 10 3, 10 4, 10 5 and 10 6 cells/ml of water. Concrete specimens were left for 7 days, 14 days and 28 days of curing. Tests were conducted for measuring properties like compressive strength, split tensile strength, flexural strength were measured in different interval of curing period. The research showed that concrete having bacterial infusion in all cell concentration have increment in strength in comparison to control mix. Maximum of 32% increase in compressive strength, 14% increase in split tensile strength and 29% increase in flexural strength were observed in the specimen having bacterial concentration of 10 5 cells/ml of water. Microbial calcite precipitation was visualized by Scanning Electron Microscopy (SEM), which showed the growth of filler materials i.e. calcite deposition inside the concrete pores, which results in denser concrete causing a rise in its strength.